First Description of Macrolide-Resistant Mycoplasma pneumoniae in Adults with Community-Acquired Pneumonia in Italy. (17th March 2019) - Loconsole, Daniela; De Robertis, Anna Lisa; Mallamaci, Rosanna; Sallustio, Anna; Morea, Anna; Prato, Rosa; Quarto, Michele; Martinelli, Domenico; Chironna, Maria
Abstract : Background . Mycoplasma pneumoniae is a common cause of community-acquired pneumonia (CAP). This cross-sectional study aimed to determine the prevalence of macrolide-resistant M. pneumoniae strains in a convenience series of 234 adult hospitalised and nonhospitalised subjects with a diagnosis of CAP in January 2013 to April 2015 in South Italy. Methods . Respiratory samples were subjected to real-time PCR. In M. pneumoniae -positive samples, domain V of 23S rRNA was sequenced to detect resistance-conferring point mutations. P1 major adhesion protein typing and multiple loci variable-number tandem repeat analysis (MLVA) were also performed. Results . Of the 234 samples, 15 (6.4%) were positive for M. pneumoniae . Three of these had a macrolide-resistant genotype: two and one had A2063G and A2064G mutations, respectively. Fourteen of the 15 strains were subtyped: half had subtype 1 and half had subtype 2. Eight strains underwent MLVA profiling: one each had the J, A, and Z type. The remainder was unclassifiable. Conclusions . This novel discovery of macrolide-resistant M. pneumoniae strains in adults with CAP in Italy suggests that there may be increasing circulation of these strains in the population. To facilitate rapid optimization of the antibiotic strategy in Italy, macrolide resistance should be monitored by a surveillance system that is based on molecular methods.